AN ANALYSIS OF FIRST YEAR STUDENTS’ ERRORS IN SOLVING MATHEMATICAL LOGIC PROBLEMS BASED ON NEWMAN’S PROCEDURE IN THE INFORMATION SYSTEMS PROGRAM - Zaini; Hardianto; M. Abrori; Fiky Anggara; Irfani Zuhrufillah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The identification of error types based on Newman’s Procedure includes reading, comprehension, transformation, process skills, and answer encoding. The objective of this study is to describe the analysis of students’ errors in solving mathematical logic problems based on Newman’s Procedure. This research adopts a descriptive qualitative approach involving first year students enrolled in the mathematical logic course within the Information Systems program. Data were collected through a diagnostic test administered to three students representing different levels of academic ability: one low ability student, one moderate ability student, and one high ability student. Students’ ability levels were measured based on tests covering compound propositional logic and logical operations. Data analysis was conducted by classifying errors at each stage of Newman’s Procedure, tracing the underlying factors contributing to these errors, and relating them to students’ logical reasoning abilities. Accordingly, the research method employed in this study is descriptive qualitative research. The resulting error classifications were subsequently used by lecturers as a basis for recommending improvements in instructional strategies. The results indicate that students with low ability made errors across all stages from K1 to K5, students with moderate ability tended to make errors at the case exploration and process skills stages, while students with high ability were able to complete all stages systematically and consistently. These findings confirm that the Newman Procedure is effective in mapping students’ thinking errors. Therefore, the implementation of differentiated learning strategies that emphasize problem comprehension, case exploration, and logical verification is recommended to enhance students’ reasoning abilities